New Science Building and Research: From Systems Biology to Theoretical Informatics - Jun You; Zongrong Li (tripleC: Communication, Capitalism & Critique)
Briefly introduced the status and related theories foundation of Theoretical Informatics (TI) and Systems Biology (SB). These two disciplines were compared and analyzed in the three aspects of the background, epistemological ap- proach, informational energy of open systems, thus demonstrating the similar attributes or characteristics of the two disci- plines, and indirectly discoursing the necessity, the rationality, the feasibility and the vital significance of the establishment and researches for TI. The paper also explores how to draw, reference SB model of development to promote the prosperity and great development of TI.